Solving the high-intensity multimodal training prescription puzzle: A systematic mapping review - Sharp, T.; Slattery, K.; Coutts, A. J.; van Gogh, M.; Ralph, L.; Wallace, L. (Sports Medicine - Open, 2024)
Background High-Intensity Multimodal Training (HIMT) refers to all styles of high-intensity combined aerobic, resistance and/or bodyweight exercise. Previous heterogeneity in exercise prescription and reporting in HIMT reduces the understanding of which factors should be considered when prescribing HIMT (e.g., exercise volume, intensity, duration). Previous studies have demonstrated positive effects of HIMT on health and performance outcomes. However, methodological disparities limit comparisons between findings. The objective of this systematic mapping review was to examine which prescriptive considerations and health and performance outcomes have been reported on in HIMT. This review also examined the quantity and trends of research conducted on HIMT.